1976
DOI: 10.1111/j.1600-0773.1976.tb03113.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hangover on Psychomotor Skills Related to Driving: Modification by Fructose and Glucose

Abstract: Thirty healthy male volunteers drank ethyl alcohol (1.75 g/kg) from 6 p. m. to 9 p. m., which resulted in hangover the next morning, and 10 subjects served as controls. The twenty subjects, who drank alcohol, received glucose or fructose during the same evening (1.0 g/kg) or on the following morning (0.5 g/kg). In the hangover phase psychomotor performance was recorded by a choice reaction test, two coordination tests and an attention test. The intensity of the hangover was graded subjectively and objectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 16 publications
1
19
1
Order By: Relevance
“…It is unclear why our result differed from those to [37] who found no correlation between hangover and psychomotor impairment the day after intoxication. We note, however, that their study was small compared to ours (30 vs. 95 participants) and thus results might have been affected by low statistical power.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…It is unclear why our result differed from those to [37] who found no correlation between hangover and psychomotor impairment the day after intoxication. We note, however, that their study was small compared to ours (30 vs. 95 participants) and thus results might have been affected by low statistical power.…”
Section: Discussioncontrasting
confidence: 99%
“…Residual effects have been found on simulated industrial work tasks [49] driving-related skills and driving [37,19,45] and simulated aircraft piloting [25,26,27,30,42,43,51,50] other studies, however, did not find occupational performance effects [10,7,8,14,33,39]. Using neurocognitive tasks, adverse effects were found for codification and identification tasks [28] immediate and delayed (1h) free recall [46] visual, memory and intellectual processing [17,24] time-reaction error in a go-no-go task [1] sustained attention/reaction time [12] and choice reaction time [24,18], although negative results were found for some neurocognitive measures [11,20,22,46].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observer-rated physical signs had a very low score, no data were presented on the value of individual signs, and Seppala et al . [57] reported that the physical signs were not valid. Chapman [46] also validated a number of individual hangover symptoms in his experimental studies but no scale development work was done.…”
Section: Measurement Of the Presence And Severity Of Alcohol Hangovermentioning
confidence: 99%
“…In order to conduct experimental investigations of determinants and behavioral correlates of hangover, a reliable and valid measure of hangover symptoms is needed for use in acute situations. Early experimental investigations of hangover using individual signs and symptoms without scale development validated certain subjective symptoms whereas objective signs of hangover were not significantly increased (Chapman, 1970;Seppala et al, 1976;Ylikahri et al, 1974).…”
Section: Introductionmentioning
confidence: 99%